Toxic Effects of Waterborne Pb Exposure on Hematological Parameters and Plasma Components in Starry Flounder, Platichthys stellatus - Min-Jung Kim; Kyung Mi Lee; Sung-Pyo Hur; Cheol Young Choi; Jun-Hwan Kim (Animals)
Lead (Pb) is a non-essential toxic metal that accumulates in aquatic environments, negatively impacting fish health. This study evaluated the acute toxicity of Pb in starry flounders (Platichthys stellatus). Fish (41 ± 8.1 g, 14 ± 0.9 cm) were exposed to Pb concentrations of 0, 10, 20, 40, 80, 160, 320, and 640 mg Pb2+/L for 96 h. The lethal concentration (96 h LC50) was determined to be 227 mg Pb2+/L. Hematological analysis showed significant decreases in RBC counts, hemoglobin, and hematocrit, while MCH and MCHC increased at ≥160 mg Pb2+/L. Plasma calcium levels significantly decreased following Pb exposure, and AST activity was reduced. These findings suggest that acute waterborne Pb exposure adversely affects survival, hematological parameters, and plasma components in P. stellatus, providing insight into Pb toxicity in aquatic organisms.